PERMAINAN VISUAL, SIMBOL, DAN PENGHARAPAN DALAM KARTU UNDANGAN PERNIKAHAN DI YOGYAKARTA - Hesti Rahayu (DeKaVe, 2011)
This study was designed in order to explain the socio- cultural relationship between the wedding invitation card created by graphic designers in Yogyakarta; to reveal the contained symbolic meanings; and to examine the considerations of which the designers decided to use certain visual composition in creating their artworks and why they did it. Hermeneutic theoretical framework was applied to accomplish the research objectives. The first step done was construing the wedding invitation cards and describing the artists' life and cultural background. The invitations then were studied by exploring its' 'socio historical elements', analyzing it visually and ended by interpreting it. This study found out that wedding invitation cards created by graphic designers in Yogyakarta were works of art that could be distinguished from the common ones which were made in a mass production. Wedding invitation card was an effect of 'inviting culture' transformation in Javanese society, from inviting verbally to inviting by written invitation. However, it did not mean that the verbal invitation tradition was vanishing. The socio- cultural relationship existed in wedding card was due to the changing in the customs and manners of inviting people. In the cards made by graphic designer artists, the socio- cultural relationship is not reflected in its visual aspects. When it does, it would be managed and adapted in such a way to meet the artists' aesthetic base that they mastered from their academic experience, i.e. Western aesthetic. The creation of visual artworks was determined by the creative process undertaken by the designers. Yet, each piece of work of visual art basically was conformed the creator's style as a mean to represent the couple and to represent his own authenticity as a graphic designer. The meaning of representation was not representing the reality but more on representing an ideal or expectation.Keywords : Visual artist - Wedding invitation cards - Simbolic meaning